Violence, Gender, and Poverty in the Context of Sweba Accusations in Burkina Faso - Burnautzki, Lydia (My University, 2024)
This article analyses the main patterns of a culture and gender specific violence phenomenon among the Mossi of Burkina Faso: The sweba phenomenon. Women are accused, deprived of their livelihood, violently expelled from their villages, and permanently socially excluded. Based on qualitative and quantitative evidence from 1965–2009 of the two biggest shelters in the capital Ouagadougou, the argument is made that sweba accusations are the main reasons for female poverty and homelessness which rose at the end of the 1980s and the beginning of the 1990s to a significant extend and led to change in social care structures. Conflicts over land use, economic interests, and a rising misogynist environment play a main role in the deprivation of women’s rights. In this context, the term “witchcraft” is part of a legitimizing discourse that helps hiding multiple forms of violence against women and must be rejected.
Keywords: Burkina Faso; homelessness; poverty; stigmatization; violence against women; ddc:300